Design of Integrated Warehouse Control Tower (WCT) Digitalization by the Internet of Things Architectures - M. Tirtana Siregar (Jurnal Penelitian Pendidikan IPA, 2023)
The problem that often occurs in information systems, especially in the logistics process, is improper management because the machine is not connected to inventory control and not integrated with the operator, so it takes a long time to analyze errors in the logistics process. This study develops warehouse logistics control information to speed up and accurate inventory processes. This study designed the Warehouse Control Tower (WCT) as a strategic development based on Wireless Sensor Network that is connected to a warehouse system and integrated with a computer connected to the RFID (Radio Frequency Identification) system, AI (Artificial Intelligence) cameras, and barcodes. Value stream mapping is used to map the process flow of warehousing activities and information flow at the level of the total warehouse process flow. Overall, the results of the analysis using the value stream mapping method indicate that the process flow using RFID and Artificial intelligence is more efficient than before implementation.